Water and Hydro Power - Varma, C. V.J. (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Water is life and energy, basic human needs. The water supply and hydropower demand scenario for India for the year 2025 shows that 90% of the area of the country falls under the Physical Water Scarcity Group. While 500kWh/year per capita energy consumption is considered to be the minimum needed to ensure a quality of life, many developing countries consume less than 76 kWh/year. Hydropower is renewable clean energy and needs to be fully exploited. In Asia and Africa, there is a great opportunity for regional cooperation in development of water resources and hydropower with which to benefit cooperating countries. Key words: Water resources; Water scarcity; Regional cooperation; Per capita electricity consumption; Electricity production capacity; India DOI: 10.3126/hn.v7i0.4228 Hydro Nepal Journal of Water, Energy and Environment Vol 7, July, 2010 Page: 17-19 Uploaded date: 31 January, 2011